(untitled) (Conference on English Language Teaching, 2023)
Linguistics is required in English language teachers since it assists teachers in explaining to pupils the English components and structures. Every language has a linguistic system or norms that may be learnt in terms of phonology, morphology, syntax, and semantics. English language teachers, on the other hand, should be integrated with other subjects such as psychology, education- cognitive science, anthropology, language acquisition, sociology, bilingualism, and language teaching. Knowing the students is critical for teachers in order to establish suitable classroom environments. The teachers must be compassionate and patient with their students, and must be able to put themselves in their shoes. In general, the goal of English teachers is to prepare students to communicate effectively and eloquently in both spoken and written formats. To accomplish this goal, the teachers must recognize that pupils are not blank slates waiting to be filled with information. The teachers can serve as a coach, mediator, or consultant, but they must allow pupils to explore, ask questions, and share their opinions. Teaching English as a foreign language necessitates a wide range of skills and tactics. An English teacher is supposed to be familiar with the pupils and the teaching objectives, as well as the subject matter, certain teaching methods, and a broad general knowledge. Furthermore, in order to be a good role model for their students, English teachers must be very motivated in their work.